Variations in Vegetation Cover in Al-Suwaira District during The period (2017-2023) Using Remote Sensing Data and Geographic Information Systems (GIS) - Khudair, Yasser Y.; Khaleefa, Ahmed A.; Hasan, Ahmed F.; Ali, Abdulrahman B.; Al-Din, Mustafa B. (Iraqi Journal of Science, 2026)
This research aims to determine the extent of change in the vegetation cover of the Al-Suwaira region in the period 2017-2023, as this region faces many problems, the most important of which are urban expansion at the expense of agricultural land, soil erosion, climate change, pollution. The region is located in southern Iraq, where water resources are scarce compared to the northern and central parts. The Support Vector Machine (SVM) classifier was applied to the seven scenes adopted in this work from Landsat 8 and Landsat 9 satellite data, and the area and percentage of each land cover category in the study area were calculated. The results indicated that the percentage of vegetation cover during 2017-2023 decreased by 1% annually using a graphical relationship between the percentages for each scene and the years. This decrease in the vegetation cover of the Al-Suwaira region is considered a dangerous indicator that threatens the ecosystem. Accordingly, the study recommends that the concerned authorities monitor the region’s ecosystem and take the necessary measures and procedures to increase the water level in the Tigris River, reclaim lands, and encourage farmers to pay attention to agriculture.